PENDUGAAN CADANGAN KARBON TEGAKAN KARET (Hevea brasiliensis) HUTAN RAKYAT BERDASARKAN KELAS UMUR DI KABUPATEN OKU TIMUR - Istomo; Yumna Nabilah (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2026)
Rubber stands (Hevea brasiliensis) not only function economically, but also have an ecological contribution as a carbon sink in the atmosphere. This study aims to estimate carbon stocks and CO₂ absorption in smallholder rubber stands based on age classes (II, IV, and V) in Karya Makmur Village (land A) and Nikan Village (land B), East OKU Regency. Data were obtained by measuring tree diameter and height in 24 plots, then calculating volume and biomass, and converting them into carbon stocks and CO₂ absorption. Statistical analysis included Spearman correlation tests and simple linear regression tests. The results of this study indicate that H. brasiliensis stands in East OKU Regency have carbon stocks and CO₂ absorption that increase with age. In land A, the highest average carbon stock was 227.46 tons/ha in KU V, with CO₂ absorption of 834.79 tons/ha. In land B, KU IV had an average carbon stock of 158.10 tons/ha and CO₂ absorption of 583.58 tons/ha. Statistical tests demonstrate a strong positive relationship between age and carbon content. This research strengthens the role of rubber community forests as a solution to climate change mitigation.